Developing Digital Pocketbook Interactive Based on HTML-5 to Improve Mathematics Learning Outcomes - Nurvidia, Delia Sonanta; Yulianto, Sigit (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
Interactive learning media have an essential role in realizing interesting and interactive mathematics learning, so they have the potential to optimize student learning outcomes. This research aims to develop and evaluate an Interactive Mathematics pocketbook in HTML5 format that can be used to improve student learning outcomes. This research and development uses a 4D model. This research found that elementary school students need and like mathematics pocketbooks that look attractive and have interactive features as a learning tool. The product validation test results obtained a final score from material and language experts of 86.47%, which means that the product reached the very feasible category regarding content quality, graphics, and language. Media experts gave a final score of 88.3%, which means that the product is very worthy in terms of content structure, appearance, ease of use, and ease of learning. The results of field trials also show that the media developed can improve student learning outcomes in the medium category with an n-gain score of 0.56. These findings indicate that the development of an Interactive Mathematics Handbook in HTML5 format with a 4D model can produce a valid and effective product used to support the learning process of elementary school students.